UNSAFE ACT AS THE RISK FACTORS OF ACCIDENTS IN USING MILL IN ROOF TILE INDUSTRY AT PEJATEN VILLAGE TABANAN REGENCY - Sutjana, D.P.; Adiputra, N. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2008)
The use of mill and hand press machines had been increased the productivity ofroof tile home industry at Pejaten Village Tabanan Regency. But the increased ofproductivity followed by increased of working accidents. Many effort had been done toreduced the accident such as equipped the mill machine with machine’s cover, footprotective devices, and training to the new employees; but, the accident still happen.Although the incident of accident was lower but the disability was severed such as loss ofhand, loss oh finger, or other physical defects of the body part. Such physical defectscaused a serious effect on worker’s daily lives and social activities. To find out the unsafeacts as the risk factors of accident, a retrospective study was done using interview and onthe spot observation to the milling process. The results are found: there are three riskfactors contributed to the accidents, namely: the human factor, the tools and theenvironment. The human factor contributed highest one for the accident. From humanfactors it was found that there are many unsafe acts, such as: careless, going up to theupper inlet of mill to push mixing raw material with foot or hand, moving the millwithout turn off the machine, cleaning the mill without turn off the mill, taking out thestone which trapped the rollers using hand, operating the machine without guarding,working with tired condition, working without knowing the operation procedure, withouttraining, improver lighting, working without personal protective devices, etc. The highestincidents come from pushing the raw materials on inlet of mill in order to speed-up themilling process. To solve the problems some actions must be done such as providing themill with the appropriate equipments; by doing so, the operator can push the materialsafely to speed-up the mill process, turn off the machine before cleaning, appropriatetraining before operating of mill, using the personal protective devices, and doing goodhouse keeping and inspection, regularly.